Transaction Processing System Analysis Using The Distribution Management System (DMS) Nexsoft Distribution 6 (ND6) - Isnawati Muslihah; Sofia Agustin Nastura (Institut Teknologi Bisnis AAS Indonesia, 2020)
Distribution Management system (DMS) is an application that manages almost the entire processing of sales orders, purchases, inventory management and financial accounting. The DMS application is only intended for specific types of distribution businesses than other types of businesses, which are at least able to provide a much higher level of functionality, specifically for the needs of distribution companies. This research was conducted at PT. Succeed which is a food distribution company. The daily transaction processing system at this company uses DMS Nexsoft Distribution 6 (ND6). NexSoft Distribution 6 (ND6) is the main operating system for any trading business in carrying out daily activities. NexSoft distribution is produced by PT. Paramadaksa Teknologi Nusantara which is a company engaged in Information Technology (IT), which is headquartered in the Tangerang area.